ПРИНЦИПИ ПОБУДОВИ І КРИТЕРІЇ ОЦІНЮВАННЯ СУЧАСНИХ ІТ - Тимчик, С. В.; Злепко, С. М. (Vinnytsia National Technical University, 2014)
In this paper, presentedprinciple of construction ІТ operating in a single information space  using the categorical approach.